Measuring anxiety in depressed patients: A comparison of the Hamilton anxiety rating scale and the DSM-5 Anxious Distress Specifier Interview. (October 2017) - Zimmerman, Mark; Martin, Jacob; Clark, Heather; McGonigal, Patrick; Harris, Lauren; Holst, Carolina Guzman
Abstract: DSM-5 included criteria for an anxious distress specifier for major depressive disorder (MDD). In the present report from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project we examined whether a measure of the specifier, the DSM-5 Anxious Distress Specifier Interview (DADSI), was as valid as the Hamilton Anxiety Scale (HAMA) as a measure of the severity of anxiety in depressed patients. Two hundred three psychiatric patients with MDD were interviewed by trained diagnostic raters who administered the Structured Clinical Interview for DSM-IV (SCID) supplemented with questions to rate the DADSI, HAMA, and Hamilton Depression Rating Scale (HAMD). The patients completed self-report measures of depression, anxiety, and irritability. Sensitivity to change was examined in 30 patients. The DADSI and HAMA were significantly correlated ( r = 0.60, p < 0.001). Both the DADSI and HAMA were more highly correlated with measures of anxiety than with measures of the other symptom domains. The HAMD was significantly more highly correlated with the HAMA than with the DADSI. For each anxiety disorder, patients with the disorder scored significantly higher on both the DADSI and HAMA than did patients with no current anxiety disorder. A large effect size of treatment was found for both measures (DADSI: d = 1.48; HAMA: d = 1.37). Both the DADSI and HAMA were valid measures of anxiety severity in depressed patients, though the HAMA was more highly confounded with measures of depression than the DADSI. The DADSI is briefer than the HAMA, and may be more feasible to use in clinical practice.